Wear Properties of Nanocomposite Traffic Marking Paint. (15th July 2018) - Taheri, Maryam; Jahanfar, Mehdi; Ogino, Kenji
Abstract : Durability and wear properties of traffic marking paints are one of the most important challenges in traffic management. This provides high-value cost-benefit, crowd reducing, improving journey times and decreasing environmental targets which are made by standing or slow-moving traffic. Because of the volume of traffic passing, climatic conditions, type of road surface, and drivers' behavior, a traffic marking paint gradually loses its basic properties such as durability and night visibility (R L ) that may potentially lead to accidents because of a loss of cognitive perception for drivers. Therefore, an effective wear resistance traffic marking paint is desirable to reduce wear, extending the lifetime and durability of paints. Analyzing this effect via microgranules, nanoclay application is the aim of this study. Clay/acrylic resin nanocomposite is synthesized using Cloisite® 30B with different percentages. Finally, production of traffic marking paint nanocomposites with this nanocomposite acrylic resins can offer the promising prospect for these aims.